Verticillium dahliae secreted protein Vd424Y is required for full virulence, targets the nucleus of plant cells, and induces cell death. (7th July 2021) - Liu, Lisen; Wang, Zhaohan; Li, Jianing; Wang, Ye; Yuan, Jiachen; Zhan, Jingjing; Wang, Peng; Lin, Yongjun; Li, Fuguang; Ge, Xiaoyang
Abstract: Fungal pathogens secrete effector proteins that regulate host immunity and can suppress basal defence mechanisms against colonization in plants. Verticillium dahliae is a widespread and destructive soilborne fungus that can cause vascular wilt disease and reduces plant yields. However, little is currently known about how the effectors secreted by V . dahliae function. In this study, we analysed and identified 34 candidate effectors in the V . dahliae secretome and found that Vd424Y, a glycoside hydrolase family 11 protein, was highly upregulated during the early stages of V . dahliae infection in cotton plants. This protein was located in the nucleus and its deletion compromised the virulence of the fungus. The transient expression of Vd424Y in Nicotiana benthamiana induced BAK1 ‐ and SOBIR1 ‐dependent cell death and activated both salicylic acid and jasmonic acid signalling. This enhanced its resistance to the oomycetes Phytophthora capsici in a way that depended on its nuclear localization signal and signal peptides. Our results demonstrate that Vd424Y is an important effector protein targeting the host nucleus to regulate and activate effector‐triggered immunity in plants. Abstract : Vd424Y is an important effector protein targeting the host nucleus to regulate and activate effector‐triggered immunity in plants.